Draft Tenth Five Year Plan (2002-2007) and Annual Plan (2002-2003) Government of Andhra Pradesh - Planning Commission (Planning Commission, 2002)
Andhra Pradesh is the fifth largest state in country with the geographical area of 274.40 lakh hectares and population of 7.57 crores according to 2001 census. The annual plan investment has gone up from Rs.188.60 crores during the Second Five Year Plan (1956-1961) period to Rs.30398.23 crores during the Ninth Five Year Plan (1997-2002) period.
Planning Department, Government of Andhra Pradesh